The mental health benefits of relationship formalisation among lesbians and gay men in same‐sex relationships. (3rd September 2015) - Bariola, Emily; Lyons, Anthony; Leonard, William
Abstract: Objectives: To examine links between same‐sex relationship formalisation – such as registered domestic partnerships and commitment ceremony unions – and mental health among lesbians and gay men, after controlling for differences in other relationship characteristics. Methods: Data were collected via an online survey of a national sample of Australian lesbians and gay men aged 16 years and older, with the sample for analysis confined to those in a same‐sex relationship (n=1, 420). The K10 Psychological Distress Scale was used as an indicator of mental health. Results: Being in a formalised relationship was associated with lower distress for those aged 16–39 years but not for those aged 40+ years; whereas, intending to formalise was associated with higher distress among the older group. These associations remained significant after controlling for cohabitation, feeling able to seek partner emotional support, relationship tenure and financial arrangements. Conclusions and implications: Relationship formalisation appears to be an important protective factor for mental health among gay men and lesbians, especially among younger sexual minority individuals. These findings suggest that affording same‐sex couples the opportunity to formalise their relationship is not only a civil rights issue but also a public health issue.